Complete F-type mitochondrial genome of freshwater mussel Lanceolaria glayana. (3rd March 2016) - Wang, Guiling; Chen, Meiling; Li, Jiale
Abstract: Lanceolaria glayana is widely distributed in China as a common species of freshwater pearl mussel. The complete F-type mitochondrial genome of L. glayana was firstly reported by this research. This circle genome (15, 736 bp in size) contains 13 protein-coding genes, 22 tRNA genes, 2rRNA genes. Most of the protein-coding genes initiated with the orthodox ATG start codon while COI and ND4 were corresponding to ATA start codon. Further, 28 non-coding regions were found throughout the mitogenome of L. glayana, ranging from 1 to 310 bp. The maximum is between ND5 and tRNA Gln (310 bp), which is longer than the control region sequences (about 280 bp) of freshwater mussels from Poland and South Korea.